2018
DOI: 10.1158/0008-5472.can-18-1772
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin F-Dependent Degradation of RBPJ Inhibits IDH1R132H-Mediated Tumorigenesis

Abstract: Cyclin F is a substrate recognition subunit of Skp1-Cul1-Fbox protein (SCF) E3 ubiquitin ligase complex. Although there have been reports describing the role of cyclin F in the genotoxic stress response, its function under conditions of altered metabolic homeostasis remain unexplored. Here we report that cyclin F is induced upon metabolic stress in a FOXO1-dependent manner. Under metabolic stress conditions, cyclin F mediated polyubiquitylation of RBPJ at Lys315, leading to its proteasomal degradation. RBPJ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Silencing of cyclin F gene expression resulted in increased tumor size and formation of numerous metastatic nodules in the lungs and liver in an in vivo mouse model. More interestingly, this depletion evidently affected epithelial and mesenchymal markers, 15 which was consistent with our observations. The primary objective of this study was to determine the impact of cyclin F-RRM2 axis downregulation on the A-375 primary melanoma cell line in terms of hallmarks of cancer progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Silencing of cyclin F gene expression resulted in increased tumor size and formation of numerous metastatic nodules in the lungs and liver in an in vivo mouse model. More interestingly, this depletion evidently affected epithelial and mesenchymal markers, 15 which was consistent with our observations. The primary objective of this study was to determine the impact of cyclin F-RRM2 axis downregulation on the A-375 primary melanoma cell line in terms of hallmarks of cancer progression.…”
Section: Discussionsupporting
confidence: 92%
“…Low cyclin F has been previously reported to promote aggressiveness of hepatocellular carcinoma and glioma cells. 12 , 15 We decided to ascertain whether downregulation of cyclin F would affect the ability of A-375 cells to migrate and invade through the basement membrane. A transwell migration assay and a Matrigel invasion assay demonstrated that depletion of cyclin F expression increases the cell’s migratory ( Figure 4A and C ) and invasive ( Figure 4B and C ) capacities.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown to limit centrosome duplication, with centrosome amplification being a hallmark of cancer. Furthermore, under conditions of metabolic stress, SCF Cyclin F was found to be induced and to mediate polyubiquitylation of RBP-Jκ, a mediator of Notch signaling, resulting in attenuation of the RBP-Jκ-dependent oncogenic function of the R132H mutant of isocitrate dehydrogenase 1 (IDH1) [16]. Consistent with its expected role in tumor suppression, the expression of cyclin F has been found to be down-regulated in hepatocellular carcinoma, with the extent of this down-regulation correlating with a range of prognostic markers and having been proposed as a prognostic indicator in this disease [17].…”
Section: Fbxo1 (Cyclin F)mentioning
confidence: 99%
“…The crucial roles of F-box proteins, including cyclin F, in tumorigenesis are gradually becoming acknowledged owing to their pivotal roles in such cases of cell cycle regulation and genome stability [189,192]. Recently, it was discovered that cyclin F is upregulated under metabolic stress conditions and inhibits tumorigenesis mediated by an oncogenic mutant form of isocitrate dehydrogenase 1 (IDH1), IDH1-R132H, in glioma [193]. Indeed, it was also reported that cyclin F is downregulated in hepatocellular carcinomas, and low cyclin F expression is correlated with poor survival and recurrence-free survival of hepatocellular carcinoma patients [194], supporting that, unlike other cyclins, cyclin F acts as a tumor suppressor and could be further investigated as a promising prognostic marker for hepatocellular carcinoma.…”
Section: Cyclin Fmentioning
confidence: 99%